Reforming Performance Appraisal for Agile Software Development Projects - Md Rejab, Mawarny; Noble, James (International Journal of Engineering and Technology, 2018)
Changes in software development methods should lead to changes in an organizationâ€™s performance appraisal system. Several organizations, however, have adopted Agile software development methods without reforming their performance appraisal. Performance appraisal should be aligned to Agile values, principles, and practices, which advocate interactions, collaborations, teamwork, and knowledge transfer. Through a Grounded Theory study involving 48 Agile practitioners and external specialists, we discovered two major changes to performance appraisal for Agile teams: integrating individual and team performance assessment criteria, and shifting from quantitative to qualitative measurement of performance. Our findings indicate that reforming performance appraisal tends to influence successful expertise coordination in Agile teams. This study can be a baseline in generating an Agile-compliant performance appraisal to assess Agile team members in a fair and consistent manner. This indirectly increases motivation amongst team members and tends to produce capable workforce to perform at a higher level.Â Â